NILAI-NILAI AKHLAK DALAM SULUK LINGLUNG DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM - Ma'arif, M. Syamsul (STAIN Kediri, 2015)
Morality remains a problem for Indonesia up to now as shown in various kinds of social problems such as violence, immorality, corruption and others. All these problems are in fact related to the morale of the nation. Education is an area which is expected to cope with all moral issues. Therefore, moral education is an important aspect which needs proper strategies and sources in order to be successful. Suluk linglung is one of the ancient works which contains a lot of moral values highly relevant for education. This paper focuses on the moral values in Suluk Linglung which portrays Sunan Kalijaga’s spiritual journey to find the essence of life and its relevance with Islamic education.Keywords: Pendidikan, Moral, Suluk Linglung